Electron and laser-based additive manufacturing of Ni-based superalloys: A review of heterogeneities in microstructure and mechanical properties - Nana Kwabena Adomako; Nima Haghdadi; Sophie Primig (Materials & Design, 2022)
The adaptation of additive manufacturing (AM) for Ni-based superalloys has gained significance in aerospace and power-generation industries due to the ability to fabricate complex, near-net-shape components on-demand and with minimal material waste. Besides its advantages, challenges remain in metal AM, especially for printing complex alloys such as superalloys. These challenges are often linked to heterogeneity in the as-fabricated parts and continue to limit the practical applications of AM products. A thorough understanding of the relationship between the complex AM process and the resulting microstructure heterogeneity needs to be established before mitigation strategies can be developed. The ability to fabricate more homogeneous Ni-based superalloy parts is expected to unlock not only better mechanical properties but also additional fields of applications.This review aims to summarize the current understanding of heterogeneities in the microstructure and mechanical properties of AM Ni-based superalloys. Microstructure heterogeneities discussed include heterogeneity in the chemical composition, phase constitution, porosity, grain and dendrite morphology, and solid-state precipitates. Related heterogeneities in hardness, tensile, creep, fatigue, and residual stress are discussed to represent mechanical properties, and mitigation strategies are summarized. The origins of heterogeneity in the as-fabricated parts are linked to the variations in AM thermal conditions caused by the complex thermal histories.